PENGARUH PELATIHAN PLYOMETRIK LOMPAT BANGKU DAN LOMPAT MELEWATI BANGKU TERHADAP DAYA LEDAK OTOT TUNGKAI - I Made Danu budhiarta (Universitas Pendidikan Ganesha, 2015)
Abstract: The Effect of Plyometric Exercise of Jumping on Benches and Jumping over Benches on Explosive Power of Leg Muscles. This study aimed at describing (1) the quality of the explosive power of the students’ leg muscles and (2) analyze the difference of explosive power of the students’ leg muscles between group of students that learn using plyometric jumping on benches and plyometric jumping over benches at Physical Health and Recreation Education Departement FOK Undiskha. This type of research belonged to a quasi experimental research. The explosive po-wer was obtained by converting the high gain scores of the vertical jump test with body weight on the basis of Lewis’ nomogram scale. Then the data were analyzed using covariance analysis by SPSS program version 17.0. The result shows that, (1) the quality of the explosive power of the stu-dents’ leg muscles was poor. (2) plyometric exercise of jumping on benches and jumping over ben-ches could improve explosive power of students’ leg muscles significantly, and (3) the improve-ment of explosive power of the students’ leg muscles with plyometric jumping on benches was bet-ter than plyometric jumping over benches (F = 7.872 dan p = 0.001 < a = 0.05). Keywords: exercise, explosive power of leg muscles, plyometric jumping on benches, plyometric jumping over benches Abstrak: Pengaruh Pelatihan Plyometrik Lompat Bangku dan Lompat Melewati Bangku ter-hadap Daya Ledak Otot Tungkai. Penelitian ini bertujuan untuk: (1) mendeskripsikan kualitas da-ya ledak otot tungkai mahasiswa dan (2) menganalisis perbedaan daya ledak otot tungkai antara ma-hasiswa yang mendapat pelatihan plyometrik lompat bangku dan lompat melewati bangku di Jurusan Penjaskesrek FOK UNDIKSHA. Jenis penelitian ini adalah penelitian kuasi eksperimen. Data daya ledak diperoleh dengan mengkonversi skor tinggi raihan dari hasil tes vertical jump dengan berat ba-dan berdasarkan skala nomogram dari Lewis. Selanjutnya data dianalisis menggunakan analisis va-rians dengan program SPSS 17,0. Hasil penelitian ini adalah (1) kualitas daya ledak otot tungkai ma-hasiswa berada dalam kategori kurang, (2) pelatihan plyometric lompat bangku dan lompat melewati bangku sama-sama dapat meningkatkan daya ledak otot tungkai mahasiswa secara signifikan, dan (3) peningkatan daya ledak otot tungkai mahasiswa dengan pelatihan plyometrik lompat bangku (PLB) lebih besar dari pada plyometrik lompat melewati bangku (PLMB) (F = 7,872 dan p = 0,001 < a = 0,05). Kata-kata Kunci: daya ledak otot tungkai, pelatihan, plyometrik lompat bangku, plyometrik lompat melewati bangku